The little toy shop - Wolfe, Frances (Tundra Books, 2008)
Mr. Kringle spends happy days helping every customer find just the right toy in his special little toy shop, and when a box arrives with a small stuffed bunny inside, Mr. Kringle is determined to find him a loving home in time for Christmas.